Arterial partial pressure of oxygen and procalcitonin levels correlate with pulmonary artery systolic pressure in patients with active pulmonary tuberculosis. (April 2022) - Wen-ting, Li; Chang-wei, Wu; De-jian, Bian; Wei, Sha
Highlights: Pulmonary tuberculosis (PTB) can cause elevated pulmonary artery systolic pressure (PASP). Studying what is correlated with PASP values in patients with active PTB. Degree of hypoxia may influence PASP in active PTB. Severity of secondary respiratory bacterial infection may influence PASP in active PTB. Abstract: Object: We aimed to study whether arterial blood gas parameters, inflammatory markers, and coagulation indicators correlate with pulmonary artery systolic pressure (PASP) values in patients with active pulmonary tuberculosis (PTB). Methods: A total of 121 patients with PTB who had a measurement of PASP by Doppler echocardiography in the active phase of tuberculosis were included in this study. We carried out univariate and multivariate linear regression analyses to determine factors correlated with PASP values. We excluded patients with other diseases or conditions that might lead to increased PASP. Results: Univariate linear regression analysis revealed positive correlations of age, white blood cell count, neutrophils ratio, Log procalcitonin, erythrocyte sedimentation rate, Log C-reactive protein, fibrinogen, Log D-dimer with PASP and showed an inverse correlation of arterial partial pressure of oxygen (PaO2 ) and arterial oxygen saturation (SaO2 ) with PASP. Multiple linear regression analysis demonstrated that PaO2 and Log procalcitonin remained correlated with PASP values. Conclusion: PaO2 and procalcitonin were strongly correlated with PASP values in patients with active PTB. The degree of hypoxia and severity of secondary respiratory bacterial infection may influence PASP value in active PTB.